Existence and uniqueness of a renormalized solution to fractional elliptic inclusions with L^1-data - Truong, Le Xuan; Trong, Nguyen Ngoc; Truong, Huynh Cao; Do, Tan Duc (Topological Methods in Nonlinear Analysis, 2025)
Let d and Ω ^d be bounded with Lipschitz boundary. We prove the existence and uniqueness of a renormalized solution to the inclusion problem \[ cases β(u) + Lu i f & in Ω, u = 0 & in Ω, cases \] where f L^1(Ω), the operator L generalizes the regional fractional p-Laplacian with 1 < p < ∞ and β is a maximal monotone operator on . A comparison between renormalized and weak solutions is also discussed.